Consumer Behavior towards Ready-to-Eat (RTE) Market: A Study of MTR Foods - Rupali Chaurasiya; Rudresh Pandey; Priyanka Verma; Xin Hui Kek; Daisy Mui Hung Kee; Xin Yi Yeoh; Pei Jia Wah; Regina Rokiah (International Journal of Applied Business and International Management, 2020)
MTR Foods is a well-known brand in the world for its packaged foods especially ready-to-eat meals. The purpose of this study is to determine the factors affecting the purchase decision of India’s and Malaysia’s consumers against the ready-to-eat (RTE) market. Online research and survey were done to collect the results. The factors influencing the consumer behavior includes price, convenience, taste, and nutrition. Most of the respondents are willing to make recommendation about MTR Foods. MTR Foods can improve its brand awareness by making more advertisement as there is around 27.9% of the respondents do not recognize the brand. Additionally, MTR Foods may conduct research in different states and countries for the company’s future planning.